First Records and Precise Documentation of Five Bark and Ambrosia Beetles (Coleoptera: Curculionidae: Scolytinae) in Albania and Montenegro - Fiala, Tomáš; Holuša, Jaroslav (Zootaxa, 2025)
Occurrence data are essential for entomological studies, especially in evaluating climate impacts on insect populations. However, knowledge is distributed unevenly across regions, with some areas of Europe receiving considerably more study than others. While Xylocleptes bispinus, Pityokteines curvidens, Xyleborus dryographus, Xyleborus eurygraphus, and Hylastes attenuatus are common bark beetles in Europe, we report the first records of Pityokteines curvidens and Hylastes attenuatus in Montenegro, along with the first record of Xyleborus eurygraphus in Albania. Additionally, we provide precise data on the occurrences of Xylocleptes bispinus and Xyleborus dryographus in Albania.